DOI: 10.17077/etd.on05jbdv
|View full text |Cite
|
Sign up to set email alerts
|

Redox behavior of magnetite in the environment

Abstract: Magnetite (Fe 3 O 4) is a commonly found in the environment and can form via several pathways, including biotic and abiotic reduction of Fe 3+ oxides and the oxidation of Fe 2+ and Fe 0. Despite extensive research, the redox behavior of magnetite is poorly understood. In previous work, the extent and kinetics of contaminant reduction by magnetite varied by several orders of magnitude between studies, two fundamentally different models are used to explain magnetite oxidation (i.e., core-shell diffusion and redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 205 publications
1
15
0
Order By: Relevance
“…In contrast, the synthetic hematite used by Gorski showed a much lower reduction potential than the Bayferrox hematite used in this study. 34 The reason for this discrepancy is unclear, but it is consistent with other work showing that synthetic hematite is generally more reactive with contaminants than the Bayferrox hematite. 31 Comparison with Electrochemically Measured Potentials.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In contrast, the synthetic hematite used by Gorski showed a much lower reduction potential than the Bayferrox hematite used in this study. 34 The reason for this discrepancy is unclear, but it is consistent with other work showing that synthetic hematite is generally more reactive with contaminants than the Bayferrox hematite. 31 Comparison with Electrochemically Measured Potentials.…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…16,22 The calculated mineral reduction potentials were further compared to previously measured or tabulated values for Fe(II) containing minerals, which are summarized in the far right column of Figure 2. The measured potentials for Fe(II) sorbed onto goethite reported by Orsetti et al 33 and for Fe(II) sorbed to synthetic hematite and magnetite reported by Gorski 34 are of particular relevance because (i) both studies used thermodynamic CRPs (i.e., redox indicators) to calculate the mineral reduction potentials and (ii) the origins of minerals used in those studies are the same as some of the minerals used here.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A preliminary test of this approach using reduction of nitrobenzene as the contaminant reaction yielded promising correlations, 21 but subsequent efforts raised fundamental questions about how the PDE electrode response relates to material structure (e.g., E OC vs x), and what electrochemical properties might be most predictive of contaminant reduction rates (e.g., E OC or i COR ). Other studies have shown good correlations between (i) magnetite stoichiometry (x) and the kinetics of nitrobenzene reduction 89,110 or U VI reduction, 111 (ii) between redox potentials of mineral suspensions determined potentiometrically with electron-transfer mediators and nitrobenzene reduction rates, 37 and (iii) between redox potentials of various iron mineral suspensions determined spectrophotometrically with chemical redox probes (CRPs) and the rates of contaminant nitro reduction and dechlorination. 39 However, this study shows that freshly synthesized magnetite can have lower E and R P with higher i COR (all of which suggest faster reduction of contaminants), even when prepared with low stoichiometry (which would suggest slower contaminant reduction rates).…”
Section: ■ Introductionmentioning
confidence: 98%
“…21,63,65 In our previous work, we tested the latter approach, but found that it did not provide sufficient accuracies due to the need for high concentrations of the compounds to achieve adequate absorbances, which altered E H values of the suspensions. 66 Here, we performed E H measurements using mediated potentiometry, a technique that combines elements of the two aforementioned approaches. In mediated potentiometry, soluble electron transfer mediators are used to facilitate redox equilibration between an aqueous system and a redox electrode performing a potentiometric (i.e., open-circuit potential) measurement.…”
Section: ■ Introductionmentioning
confidence: 99%